Add / Minus Three Numbers
9+9-1=8-5+0=6-5-1=8-4+5=
4-4+0=5-0+4=6-2+6=7+5-2=
7+5+4=1+1+2=2+8-2=8-6+1=
7+2-9=6-3-2=9+8+7=3-1+9=
3+5+9=6+2-0=9+7+8=9+7-8=
9-1+3=7-3+1=9-3+3=9-2-2=
8+9-3=9-4+5=8-1+7=7+8+9=
3+6-6=7+4+9=5+8+4=9-4+8=
9+8-7=9-5+8=1+2-1=2-2+2=
6+2-8=7+7-5=7-3+2=8+3-3=
2+9-7=8+2+5=1+3+4=9-5-1=
8+9-8=1+2+9=8+2+4=9+5-2=
5-3+5=1+3+3=6+3+4=9+2+2=
6+7+8=9+6+8=8-2+6=7-2+6=
4+7+1=3-2+1=9+4-2=5+2+6=
4-2+6=3-2+9=9-7+8=5+2+4=
4+3+8=9-7+1=6+8+3=3+9-7=
6+4+9=6-1-4=9+4-6=7+4-7=
7+1-3=2+8+5=7-1+6=7-7+9=
7+6+1=8+1+4=4-1+7=8+2+9=
2-2+6=9-9+3=1+5+1=9+6-1=